A new approach towards analysis of life cycle of energy storage systems: An intuitionistic fuzzy rough based TODIM approach - Hussain, Amir; Ullah, Kifayat; Aydin, Nezir; Olanrewaju, Oludolapo Akanni (ELSEVIER, 2025)
The role of energy storage systems (ESS) in balancing supply and demand, integrating renewable sources, and enhancing stability is crucial. The life cycle of the ESS may vary due to the involvement of multiple environmental, economic, and social factors. During the life cycle analysis (LCA) of the ESS, the evaluation of these factors is very important. This study conducts a thorough and comprehensive analysis of the life cycles of various energy storage technologies based on multiple factors. A well-known framework called intuitionist fuzzy rough set (IFRS) is utilized to extract information from experts for ESS based on multiple factors. Then, an acronym in Portuguese for interactive and multi-criteria decision-making (TODIM) is utilized for symmetric LCA for ESS. The results, which varied using different weights, were compared with similar models to demonstrate the robustness and adaptability of the approach.
Keywords: Energy storage systems; Multi-attribute decision-making; Uncertainty handling; CHALLENGES; BATTERIES; Energy & Fuels